1995
DOI: 10.1002/mpo.2950250307
|View full text |Cite
|
Sign up to set email alerts
|

Childhood acute lymphoblastic leukemia in India: An approach to managementin a three‐tier society

Abstract: Within a population of 882 million, six thousand children will develop acute lymphoblastic leukemia each year in India. These children come from three socio-economic backgrounds: Profile I (70%) being extremely poor who cannot afford any treatment unless it is provided free, Profile II (25%) from the middle class, and Profile III (5%) who can afford to have the best possible treatment. Current protocols for childhood ALL range from simple low-cost regimes like UKALL VIII, intermediate intensity regimes like BF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…1 With 20 million carriers for thalassemia and 10 000 children being born with thalassemia major each year, if one-third of these patients have an HLA-matched sibling donor, there is a potential to cure 3000 children with BMT. 2 If one considers six per million as the incidence of aplastic anemia, there would be 6000 new cases/year, and if 10% of these patients are suitable candidates for transplant, then the country would need to do 600 transplants per year for this disease alone.…”
Section: Introductionmentioning
confidence: 99%
“…1 With 20 million carriers for thalassemia and 10 000 children being born with thalassemia major each year, if one-third of these patients have an HLA-matched sibling donor, there is a potential to cure 3000 children with BMT. 2 If one considers six per million as the incidence of aplastic anemia, there would be 6000 new cases/year, and if 10% of these patients are suitable candidates for transplant, then the country would need to do 600 transplants per year for this disease alone.…”
Section: Introductionmentioning
confidence: 99%
“…However, in developing countries where state funding for expensive health-care interventions is lacking, it is important that treatment modifications should be cost effective. 5 This is a retrospective analysis of the outcome of 210 adult patients with ALL (X15 years) treated with a modified German ALL (GMALL) protocol from 1994 to 2003. The aim of this study was to identify biologic and clinical prognostic markers for adult ALL in the Indian population and compare this with Caucasian data.…”
mentioning
confidence: 99%
“…2 We have previously reported that the expression of FRb is limited to the myelomonocytic lineage and that its expression is increased during neutrophil maturation and during the activation of macrophage; 3,4 however, among normal hematopoietic cells, only the receptor expressed in activated macrophage is functional in having the ability to bind folate. 4,5 FRb is also expressed in a functional form in approximately 70% of acute myelogenous leukemia (AML) in which it is frequently coexpressed with CD34. 6 These observations suggest that FRb is a potential target for drug delivery to AML cells, but prospects of its clinical utility are limited by the variable and the frequently low expression of the receptor in the leukemic cells of AML patients.…”
mentioning
confidence: 99%
See 2 more Smart Citations